Pellitorine, a potential anti-cancer lead compound against HL60 and MCT-7 cell lines and microbial transformation of piperine from Piper nigrum. - Ee , Gwendoline Cheng Lian; Lim, Chyi Meei; Rahmani, Mawardi; Shaari, Khozirah; Bong, Choon Fah Joseph (MDPI, 2010)
Pellitorine (1), which was isolated from the roots of Piper nigrum, showed strong cytotoxic activities against HL60 and MCT-7 cell lines. Microbial transformation of piperine (2) gave a new compound 5-[3,4-(methylenedioxy)phenyl]-pent-2-ene piperidine (3). Two other alkaloids were also found from Piper nigrum. They are (E)-1-[3’,4’- (methylenedioxy)cinnamoyl]piperidine (4) and 2,4-tetradecadienoic acid isobutyl amide (5). These compounds were isolated using chromatographic methods and their structures were elucidated using MS, IR and NMR techniques.